PERBANDINGAN WAKTU INDUKSI, DURASI DAN PEMULIHAN ANESTESI DENGAN PENAMBAHAN PREMEDIKASI ATROPIN-XYLAZIN DAN ATROPINDIAZEPAM UNTUK ANESTESI UMUM KETAMIN PADA BURUNG MERPATI (COLUMBA LIVIA) - Gorda, I Wayan; Wardita, A.A. Gde Jaya (Buletin Veteriner Udayana, 2012)
The aim of this study is to determine the comparison of induction, duration and recoverytime of anaesthesia with addition of premedication atropine-xylazine and atropinediazepamfor anaesthesia of ketamine in pigeon (Columba livia).Complete Random Device (RAL) was used to analisis. The total of eight teen of pigeonused for this study. They were divided into three groups i.e. (I) treated with ketamine : 75mg/kg of body weight as a positive control, (II) treated with combination of atropinexylazine-ketamine with dose 0,02 mg/kg of body weight, 4 mg/kg of body weight and 75mg/kg of body weight and (III) treated with combination of atropine-diazepam-ketaminewith dose 0,02 mg/kg of body weight, 2,5 mg/kg of body weight and 75 mg/kg of bodyweight. Data were analized with Analysis of Variance. (Steel and Torrie, 1989). Theresult showed that the anaesthesia of ketamine and the combination of atropine-diazepamketaminewas not resulted the induction and duration time of anaesthesia. That mean,recovery time of anaesthesia ketamine and the combination of atropine-diazepam-ketamineare 114,4 minutes and 138,1 minutes. The combination of atropine-xylazine-ketamine wasresulting the mean of induction 13,4 minutes, duration 82,8 minutes and recovery 139,6minutes. The result showed that no significantly different (P > 0.05) the time of recoverybetween the anaesthesia of ketamine, combination of atropine-xylazine-ketamine andcombination of atropine-diazepam-ketamine.
Keywords: atropine, xylazine, diazepam, ketamine, indunction, duration, recovery time, pigeon